2021
DOI: 10.3390/ijerph18041944
|View full text |Cite
|
Sign up to set email alerts
|

Key Physical Factors in the Serve Velocity of Male Professional Wheelchair Tennis Players

Abstract: The aim of this study was to identify the physical factors related to serve speed in male professional wheelchair tennis players (WT). Nine best nationally-ranked Spanish male wheelchair tennis players (38.35 ± 11.28 years, 63.77 ± 7.01 kg.) completed a neuromuscular test battery consisting of: isometric handgrip strength; serve velocity; 5, 10 and 20 m sprint (with and without racket); agility (with and without racket); medicine ball throw (serve, forehand and backhand movements); and an incremental endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…On the one hand, forces applied on the rims determine both the velocity and direction of locomotion [ 9 ], and the low effectiveness of force application could result in an ineffective push technique, as well as acting as a possible cause of injury [ 10 ]. On the other hand, previous studies have shown a grip strength correlation of 0.58 with service speed [ 13 ]. The serve is one of the most important strokes in the modern game [ 31 ], and an increasing serve speed reduces the time required for the opponent to successfully return the ball and increases the probability of the server’s dominance in the rally or of winning a direct point [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the one hand, forces applied on the rims determine both the velocity and direction of locomotion [ 9 ], and the low effectiveness of force application could result in an ineffective push technique, as well as acting as a possible cause of injury [ 10 ]. On the other hand, previous studies have shown a grip strength correlation of 0.58 with service speed [ 13 ]. The serve is one of the most important strokes in the modern game [ 31 ], and an increasing serve speed reduces the time required for the opponent to successfully return the ball and increases the probability of the server’s dominance in the rally or of winning a direct point [ 32 ].…”
Section: Discussionmentioning
confidence: 95%
“…Moreover, propelling the wheelchair while holding a racket has a negative influence on the velocity of movement [ 9 , 12 ], which may be due to an ineffective push technique resulting in the low effectiveness of force application [ 9 ], as well as being a possible cause of injury [ 10 ]. Moreover, previous studies have shown a hand strength correlation of 0.58 with service speed [ 13 ]. In this sense, the fact that hand strength values may decrease throughout successive matches could compromise the physical performance of WT players and affect the mechanics of stroke production in terms of accuracy and power [ 14 ]; however, scientific investigations of this sport and this topic are scarce compared with other sports.…”
Section: Introductionmentioning
confidence: 99%
“…The best time in seconds (sec) was recorded in a Microsoft Windows ® Excel template (Redmond, WA, USA). Chronojump Photocell ® (Chronojump, Barcelona, Spain) and Chronojump software version 1.7.1.8 were used to measure the time [ 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The values of BSR athletes range from 14.74±1.65s (Granados Domínguez et al, 2016) to 15.3±1.2s (Romarate et al, 2020). In relation to other wheelchair sports and the agility test, there is a study conducted on nine elite tennis players, where the Ttest was used, whose results were 12.42±0.99s (Sánchez-Pay et al, 2021). When comparing the data presented above in relation to BSR, it can be inferred that BSR athletes present to be slower compared to tennis players.…”
Section: Table 4 Most Used Test According To the Literature Investigatedmentioning
confidence: 99%